In vitro activity of Brucella melitensis isolates to various antimicrobials in Turkey - Denk, Affan; Demirdag, Kutbettin; Kalkan, Ahmet; Ozden, Mehmet; Cetinkaya, Burhan; Kilic, Suleyman S. (Taylor & Francis Ltd, 2015)
Background: Brucellosis is a systemic infectious disease caused by Brucella bacteria. A successful treatment requires antibiotics that can penetrate into the cell at high concentrations. The aim of this study was to assess the biotype and in vitro activity of 80 Brucella isolates obtained from blood against various antimicrobials for human brucellosis in Turkey. Methods: Identification of the types of the species designated Brucella species was made using the polymerase chain reaction (PCR), with type-specific primers. Serotyping was performed using mono-specific A and M antisera. The minimum inhibitory concentrations (MICs) of antibiotics known to have good intracellular penetration (doxycycline, rifampicin, ofloxacin, levofloxacin, moxifloxacin, clarithromycin, and azithromycin) were determined by the agar dilution method. Results: All of the 80 Brucella isolates were determined to be Brucella melitensis : 75 B. melitensis biotype 3 (93.7%) and 5 B. melitensis biotype 1 (6.3%). Doxycycline was the most effective among the tested antibiotics against Brucella species (MIC50-MIC90, 0.25-0.5 mu g/ml), and it was followed by levofloxacin (MIC50-MIC90, 0.5-1 mu g/ml), moxifloxacin (MIC50-MIC90, 1-1 mu g/ml), ofloxacin (MIC50-MIC90, 1-1 mu g/ml), rifampicin (MIC50-MIC90, 2-4 mu g/ml), azithromycin (MIC50-MIC90, 4-8 mu g/ml), and clarithromycin (MIC50-MIC90, 8-32 mu g/ml), respectively. Conclusions: The in vitro activity of doxycycline and rifampicin, which are used in the classic treatment of brucellosis, was found to be very good. Quinolones were found to have in vitro activity against Brucella isolates. Among the macrolides, azithromycin had a higher level of activity compared with clarithromycin. A combination of quinolones and azithromycin could be an alternative to doxycycline and rifampicin in the treatment of brucellosis.
Keywords: Brucella; biotype; in vitro activity; brucellosis; antimicrobial activity